Diet High in Alcohol Impacts the Gut Microbiota and Associated Metabolome (P08-134-19). (24th October 2019) - Ru, Yuan; Wang, Ninglin; Wang, Xuemiao; Zhao, Xueyin; Min, Yan; Ann, Hsing; Shankuan, Zhu
Abstract: Objectives: To examine associations between plasma metabolites and the gut microbiota with dietary patterns in a general Chinese population. Methods: The study group included 214 Chinese adults (105 men and 109 women, 50.93 ± 13.6 y) from the Wellness Living Laboratory (WELL) - China. Dietary data were collected through a validated food frequency questionnaire, and a k-means cluster analysis was performed to identify dietary patterns. An ultrahigh-performance liquid chromatography tandem mass spectroscopy was used to assess plasma metabolic profiles (759 metabolites). The gut microbiota data were analyzed using a 16 s rRNA sequencing. Results: Based on the energy contribution of each food group, 3 dietary patterns were identified as the Chinese traditional diet, the high alcohol diet, and the modern diet. Overall, 7 metabolites were found significantly higher (ANCOVA < 0.05 adjusting for age, sex, use of medication, and body mass index, FDR < 0.05) in the alcohol diet than in the traditional diet. Of these, 1, 3, 7-trimethylurate, androstenediol, nicotinamide riboside, N2, N5-diacetylornithine had a significant impact on the gut microbiota. Participants with high alcohol intake showed a significant depletion in Clostridum_XIVa (Log2FodChange = −26.3, P < 0.0001) and 4 unknown genera (Log2FodChange > −18, P < 0.0001) and enrichment in Gemmiger (Log2FodChange = 11.1, P < 0.0001) and Clostridium_XIVb (Log2FodChange = 14.0, P < 0.0001). Besides, Gemmiger ( P = 0.003) and Clostridium_XIVb ( P < 0.0001) were significantly overrepresented in participants who had high androstenediol, whereas Clostridum_XIVa was underrepresented in those who had high 1, 3, 7-trimethylurate ( P = 0.0004), androstenediol ( P < 0.0001), and nicotinamide riboside ( P < 0.0001). No significant difference was found in metabolites between the traditional diet and the modern diet. Conclusions: The pattern of alcohol diet were shown to be associated with both plasma metabolomics and the gut microbiota data. More data is needed to identify the unknown genera and to explore the pathways. Funding Sources: Initial funding for the Stanford WELL was provided by Amway via an unrestricted gift through the Nutrilite Health Institute Wellness Fund. Other funding sources included the Cyrus Tang Foundation, and the Zhejiang University Education Foundation.